The Knowledge on Autism Spectrum Disorder among Preschool Teachers in selected Schools - Shrestha, Rhinu; Dhakal, Swikri (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder. Lately, prevalence of ASD is increasing alarmingly . There is a need of adequate knowledge of ASD among preschool teachers as they are expected to play a crucial role in early detection. The objective of the study was to assess the knowledge of ASD among preschool teachers of selected schools of Budhanilakantha.Methods: A descriptive cross-sectional study was conducted using total enumeration method among 105 preschool teachers of Budhanilakantha-10. The study was conducted from 2080-9-15 to 2080-9-29. Data analysis and interpretation were done using inferential statistics and presented in tabulated form.Results: More than half (54.3%) of preschool teachers had inadequate knowledge ,while less than half (45.7%) of the population had adequate knowledge regarding ASD. Level of knowledge of respondents was found significantly associated with type of school (p = 0.038), training (p = 0.028) and exposed to autistic child (p